MAPPING TINGKAT KERAWANAN COVID-19 DAN FAKTOR AKSELERATOR PENYEBARAN VIRUS ANTAR DAERAH DI INDONESIA DENGAN MENGGUNAKAN ANALISIS CLUSTER HIERARKI - Nur Silviyah Rahmi (Politeknik Statistika STIS, 2020)
Currently the corona virus pandemic is forcing the government to formulate and implement unusual policies. Moreover, the impact of this pandemic was not only felt by the health sector, but also hit other sectors such as the economy, education, social and tourism. To prevent a bigger impact, it is necessary to group the regions based on the factors that accelerate the spread of the corona virus so that appropriate policies can be formulated for each region. It is because the demographic and cultural conditions between regions in Indonesia are different. Based on this background, the purpose of this research is to find out a map of the level of pandemic vulnerability in each area accompanied by the accelerator factor of the spread of the corona virus using the hierarchical cluster analysis method. Hierarchical cluster analysis is a multivariate technique for grouping objects based on their characteristics. Cluster analysis classifies objects so that each object that has similar properties will be grouped into one cluster. The accelerator factors referred are age, hand washing kebiasaans, work activities, and aspects of traveling. The results show that the 4 variables accelerating of the virus spread, are need attention. The provinces of Papua, West Papua, Riau, and Riau Islands are in the safe category, but from the age factor of the population, these areas are still classified as alert. This means that if the age factor is not given special attention, the four provinces have the potential to increase their status to be alert or even vulnerable. The results of this analysis are expected to provide information regarding the state of vulnerability of each region and can serve as suggestions for the government in making appropriate policies.